LANGUAGE POLICY, NATIONAL IDENTITY AND POLITICS - Minasyan Armenui (European Scientific Journal, ESJ, 2014)
The abstract dwells upon the mechanisms of language policy change in concern with national identity feeling as used in the pursuit of political dominance. Every day some languages are dying out, others are spreading its influence around. To believe that it’s a natural development of a language is absurd because the decision on a language destiny (to develop or go extinct) is determined by the political, economic and social conjunctions of an area. On the one hand, historically comes that political dominance moves forward and shapes the phenomenon of lingua franca. The English language, alike as the Russian (or Spanish and others), achieved the status of a lingua franca ‘colonising’ regions around. Language ‘colonisation’ process mainly consisted of implementation of the language of the dominating party into the conquered region and, thus diminishing the significance of the local language. As soon as the local language is given the second or third priority, this serves a sign that the local population is ready to be overtaken by another culture. Such political tricks were used by Great Britain, later the United States of America in the XX c., Soviet Union, Spain, France, etc. On the other hand, local languages or language varieties (and other social conjunctions, such as national identity) are used today (usually by the side of the opposition) to bring about changes in the political situation and people’s mentality. Many regions today are striving to revive their languages realizing the significance of their culture and national unity which might be well manipulated for the political reasons. The significant role that political and social conjunctions are playing in shaping the language policy and national identity around the world, unfortunately, is very often underestimated.